PTCa/PEEK composite acoustic emission sensors - Sakamoto, Walter K. [UNESP]; Malmonge, José A. [UNESP]; Malmonge, Luiz F. [UNESP]; Da Silva, Alberto F.G. [UNESP]; Higuti, Ricardo T. [UNESP] (My University, 2006)
Composites made of Calcium-modified lead titanate (PTCa) and poly (ether-etherketone) (PEEK) high performance polymer matrix were prepared in the film form using a hot press. The ceramic volume fraction reaches up to 60 percent providing a composite with 0-3 and 1-3 mixed connectivities due to the high ceramic content and the resulting materials could be considered PEEK-bonded PTCa particulate composite. The composites were characterized using piezoelectric spectroscopy and ultrasonic immersion techniques. Values up to 38.5 pC/N were obtained for the longitudinal d33 piezoelectric coefficient. The composite was surface-mounted on a carbon fiber plate-like specimen and the ability of the PTCa/PEEK composite to detect acoustic emission (AE) is reported. © 2006 IEEE.
Keywords: Acoustic emission; Calcium-modified lead titanate (PTCa); Connectivity; Piezoelectric polymer composites; Piezoelectric transducers; Poly (ether-ether-ketone) (PEEK); Sensors; Sielectric strength; Acoustic emissions; Organic polymers; Piezoelectricity; Volume fraction; Dielectric strength